Кремлевские свадьбы и банкеты - Краскова Валентина Сергеевна (Литература, 1997)
Экземпляры: ф.7 (1997) / Инвентарный номер: 39993 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 78 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-4